Global trends and research mental health counseling: a bibliometrics analysis - Ifdil, Ifdil; Zola, Nilma; Pratiwi Fadli, Rima; Zatrahadi, M. Fahli (COUNS-EDU: The International Journal of Counseling and Education, 2023)
The topic of mental health counseling is one that is now being explored quite a bit. The significance of preserving mental health is becoming increasingly clear to people. We use network visualization and quantitative bibliometric analysis to identify research trends and focus areas. We hope that this research will serve as a guide for upcoming follow-up research by outlining trends in mental health counseling research. The Scopus database's relevant English publications were taken out. The coauthorship networks of authors, nations, and the cooccurrence networks of author keywords were constructed using VOSviewer (version 1.6.17). We analyzed 452 articles published using the term "mental health counseling" from 1965 to 2022. The number of scientific articles related to mental health counseling jumped quite sharply in 2021 with a total of 52 documents. The top three earning authors are: Myers, B., Sorsdahl, and Lund, C. Some of the newest keywords that have emerged include: covid-19, counselor education, clinical mental health counseling, therapy, stress, mindfulness, self-care, substance use, psychological distress.